AYURVEDA, AN APPROPRIATE STRATEGY FOR SOCIAL HEALTH: An overview of the Indian Panorama - Bijoy, C. R. (Medknow Publications & Media Pvt Ltd, 1981)
The rationale for the thought of an appropriate strategy for social health, issues from the failiure to provide health with social Justice. Too much has been said and done along a devious path by the dominant class, that, increasing marginal rate of disutility threatens the very existence of man. A modest attempt has been made here to expose the corrosion in values and priorities and as to what little should and could be done to safeguard the right to health of underprivileged mass, in the light of the lack of political will and the rise of ‘elitism’ among the responsible people, the social relevance and the natural direction of progress consistent with the values and priorities of Ayurveda as a holistic system of health.